Diverse but Concentrated: Perceptions of Communicators on the Pluralism of Digital Media in Chile [Diversos Pero Concentrados: Percepciones de Comunicadores Sobre el Pluralismo de Los Medios Digitales en chile1 - Del Valle-Orellana, N (Universidad de Chile, 2020)
This article analyzes the perceptions of communicators of digital media according to their discourses on the situation of media pluralism in Chile. The opinions of the communicators were collected through 19 interviews that reveal the subjective conditions of different digital media in the country. The obtained results indicate that journalists understand media pluralism as a media diversity. Also, they consider their own media as pluralistic internally, even when it is perceived that the pluralism of the media system as a whole is limited by the commercialization of the media and the power of money over editorial lines. © 2020 Universidad de Chile. All rights reserved.